Vegetation structure drives mixed-species flock interaction strength and nuclear species roles. (30th October 2020) - Jones, Harrison H; Robinson, Scott K
Abstract: Mixed-species flocks are a key facilitative interaction for tropical birds. Forest fragmentation leads to species loss and spatial turnover in these flocks, yet it is unknown how these changes to composition influence within-flock species interactions. We used network analysis to characterize flocking interactions along a fragment-size gradient in the Colombian Western Andes. We asked 1) how patch size, edge density, and vegetation structure explained network measures indicative of flock cohesion, 2) whether changes were driven by flocking species turnover or changes to the frequency of species co-occurrence, and 3) whether nuclear species, those that maintain flock stability and cohesion, changed in importance across the gradient. We constructed weighted social networks from flock compositions observed on 500-m transects, and then calculated global network measures and the centrality of six nuclear species. Patch size and edge density did not correlate with interspecific co-occurrence patterns, but interaction strength increased with canopy height. Flocks contained numerous, weak interactions, and there were no flock subtypes, suggesting flock composition was dynamic and unstructured. Several redundant nuclear species were present and varied in importance based on ecological conditions. A chlorospingus (Passerellidae) was most central in old-growth forest, whereas several tanager (Thraupidae) species became more central in smaller fragments and disturbed forest. When partitioning network dissimilarity, we found that 66% of dissimilarity resulted from species turnover, whereas only 34% resulted from changes to species co-occurrence. This finding suggests that coherence of flocking behavior itself is maintained even as extensive species turnover occurs from continuous forest to small fragments. Abstract : Forest fragmentation negatively affects the number of species that occur in mixed-species flocks of forest birds, but its effects on the interactions between species remain poorly known, particularly in tropical montane ecosystems. Contrary to lowland flocks, we found that montane flocks were resilient to fragmentation due to the open membership nature of the interactions and numerous, redundant nuclear species. Most changes to flocking behavior instead resulted from extensive species replacement from continuous forest to fragments.